2012
DOI: 10.1371/journal.pntd.0001853
|View full text |Cite
|
Sign up to set email alerts
|

Whole Genome Analysis of Leptospira licerasiae Provides Insight into Leptospiral Evolution and Pathogenicity

Abstract: The whole genome analysis of two strains of the first intermediately pathogenic leptospiral species to be sequenced (Leptospira licerasiae strains VAR010 and MMD0835) provides insight into their pathogenic potential and deepens our understanding of leptospiral evolution. Comparative analysis of eight leptospiral genomes shows the existence of a core leptospiral genome comprising 1547 genes and 452 conserved genes restricted to infectious species (including L. licerasiae) that are likely to be pathogenicity-rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
75
0
14

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(93 citation statements)
references
References 97 publications
4
75
0
14
Order By: Relevance
“…Data from ongoing projects to obtain whole-genome sequences from a variety of Leptospira strains will aid in the analysis of candidate cis-and trans-acting factors that underlie the genetic regulatory circuitry controlling expression of leptospiral genes (65)(66)(67)(68)(69)(70). One outcome of these efforts is the computational identification of potential riboswitches, including those bound by cobalamin and thiamine pyrophosphate (68,71). Here we have presented experimental evidence for an RNA-based cis-acting element that controls gene expression in L. interrogans in response to temperature changes.…”
Section: Discussionmentioning
confidence: 99%
“…Data from ongoing projects to obtain whole-genome sequences from a variety of Leptospira strains will aid in the analysis of candidate cis-and trans-acting factors that underlie the genetic regulatory circuitry controlling expression of leptospiral genes (65)(66)(67)(68)(69)(70). One outcome of these efforts is the computational identification of potential riboswitches, including those bound by cobalamin and thiamine pyrophosphate (68,71). Here we have presented experimental evidence for an RNA-based cis-acting element that controls gene expression in L. interrogans in response to temperature changes.…”
Section: Discussionmentioning
confidence: 99%
“…Leptospires can be broadly divided into host-associated species (including pathogens and the closely related intermediate species [1]) and free-living saprophytes, and Picardeau et al proposed that the host-associated species may have evolved from a free-living progenitor (2). Therefore, comparisons between species with different ecological niches may elucidate the mechanisms that allow host-associated species to infect, persist in, and sometimes cause fatal disease in their hosts.…”
mentioning
confidence: 99%
“…L. fainei was successively cultured from two human patients with Weil's disease and antibody titers have been found in sera from cattle in Australia, France and Indonesia ( Chappel et al, 1996;Petersen et al, 2001). L. wolffii was identified as a potential pathogenic species, detected in infected humans, in sheep sera and dogs urine and can be potentially pathogenic to human and probably animal hosts (Zakeri et al, 2010); and L. licerasiae causes mild disease in humans and has been isolated from peridomestic and wild rodents and marsupials in Peruvian Amazon (Matthias et al, 2008;Ricaldi et al, 2012) and from environmental water (Saito et al, 2013). Krull et al (2015) showed that early BDD lesions had minimal populations of Treponema spp.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to Treponema species that fail to have significant genetic capabilities to break down the skin barrier (Krull et al, 2015), L. interrogans, the most common genotype in pathogenic Leptospira species, encodes a collagenase (colA gene), which was recently related to invasiveness and transmission of the spirochetes in cell monolayers and animals, being characterized as a novel and crucial virulence factor (Kassegne et al, 2014). Ricaldi et al (2012) …”
Section: Discussionmentioning
confidence: 99%